JENIS TUMBUHAN SEBAGAI PEWARNA ALAM PADA BEBERAPA PERUSAHAN TENUN DI GIANYAR - Pande Ketut Sutara (Environmental Research Center (PPLH) of Udayana University, 2009)
The aim of this research is to find out species, organ, processing method and type of color that are created by natural coloring plants for woven fabric in weaving factory namely Puri Bali, Setia and Dewi Karya. This research was conducted from March until August 2008 . This research employed purposive sampling methods, which include : interview, observation and identification of plant species used for natural coloring in woven fabric. It was found in this reseach, 28 plant species that include in 19 families which were used as natural coloring and was distributed on all plant organs. Coloring process for woven fiber/fabric was done by dipping the fiber into plant extract solution , and then fixation in CaCO3 solution , followed by washing in water and the drying out. From 3 factories observed, the factory that utilized the most natural plants color is Setia Factory which employed 17 plant species and Dewi Karya employed 15 plant species. Among those three factories, some naturally coloring plants were the same but some other plants were different.